2017
DOI: 10.1111/ecoj.12435
|View full text |Cite
|
Sign up to set email alerts
|

On the International Spillovers of US Quantitative Easing

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(165 citation statements)
references
References 47 publications
8
136
3
3
Order By: Relevance
“…Second, this paper is also related to the literature on the spillovers from US monetary policy to global financial markets (see Craine and Martin, 2008;Ehrmann and Fratzscher, 2009;Wongswan, 2009;Neely, 2010;Hausman and Wongswan, 2011;Gurkaynak and Wright, 2011;Fratzscher et al, 2013;Moore et al, 2013;Rogers et al, 2014). These papers study the effects of US monetary policy shocks on other countries' equity and bond markets, capital flows and exchange rates, typically at high frequency.…”
Section: Introductionmentioning
confidence: 96%
“…Second, this paper is also related to the literature on the spillovers from US monetary policy to global financial markets (see Craine and Martin, 2008;Ehrmann and Fratzscher, 2009;Wongswan, 2009;Neely, 2010;Hausman and Wongswan, 2011;Gurkaynak and Wright, 2011;Fratzscher et al, 2013;Moore et al, 2013;Rogers et al, 2014). These papers study the effects of US monetary policy shocks on other countries' equity and bond markets, capital flows and exchange rates, typically at high frequency.…”
Section: Introductionmentioning
confidence: 96%
“…In a followup paper, Bauer and Neely (2014) use dynamic term structure models to parse out the extent to which the declines in foreign interest rates occurred through the signaling or portfolio rebalancing channels and find evidence that both channels were in operation. Our paper is also related to the recent work of Fratzscher et al (2013) and Bowman et al (2015); the former paper systematically analyzes the global spillovers of the Federal Reserve's asset purchase programs on a broad array of financial asset prices, while the latter study empirically quantifies the spillover effects of US unconventional policies on emerging market economies. The key takeaway of these two papers is that US unconventional monetary policy measures induced a significant portfolio reallocation among investors and led to a notable repricing of risk in global financial markets.…”
Section: Consistent With This Predictionmentioning
confidence: 99%
“…Empirical studies have shown that quantitative easing has accelerated the flow of capital into less economically developed countries beyond reasonable bounds (Fratzscher, Lo Duca, and Straub 2013). From within the Keynesian paradigm, quantitative easing was criticized on the grounds that with long-term bonds removed from their portfolios, investors would spend too much in other areas, which could lead to the overvaluation of certain assets and the associated bubble behavior (Palley 2011).…”
Section: Literature Reviewmentioning
confidence: 99%